2015
DOI: 10.1016/j.jcma.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of genetic studies of thyroid disorders in Taiwan

Abstract: A systematic review of genetic studies of thyroid disorders in Taiwan identified studies of gene mutations involved in the synthesis and binding of thyroid hormone, as well as mutations of proto-oncogenes and tumor suppressor genes in thyroid cancer. Studies related to gene polymorphisms in patients with autoimmune thyroid disease (AITD) and thyroid cancer were also reviewed. The most prevalent mutations in the Han-Chinese population were c.2268insT in the thyroid peroxidase (TPO) gene and c.919-2A>G in the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Other studies have not demonstrated a significant influence of variation in the gene for this enzyme on T4 requirement in hypothyroid patients [48], or on patient-reported outcomes on (or preference for) treatment with LT4 + T3 combination therapy [49]. Further research will be needed to confirm whether genetic variations in deiodinases, and indeed in other sites of cellular access or action of thyroid hormones (such as membrane transporters, nuclear receptors and other sites) may facilitate individualised treatment of hypothyroid patients in the future [44,[50][51][52].…”
Section: Possible Explanations For Continuing Symptoms Despite 'Adequmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have not demonstrated a significant influence of variation in the gene for this enzyme on T4 requirement in hypothyroid patients [48], or on patient-reported outcomes on (or preference for) treatment with LT4 + T3 combination therapy [49]. Further research will be needed to confirm whether genetic variations in deiodinases, and indeed in other sites of cellular access or action of thyroid hormones (such as membrane transporters, nuclear receptors and other sites) may facilitate individualised treatment of hypothyroid patients in the future [44,[50][51][52].…”
Section: Possible Explanations For Continuing Symptoms Despite 'Adequmentioning
confidence: 99%
“…Symptoms associated with hypothyroidism are often non-specific in nature, and common within the euthyroid population, as described above, and a systematic and careful approach is needed to evaluate any association between the patient's symptoms and thyroid status [52]. Box1 and Figure 1 summarise a pragmatic approach to managing these patients, with individual steps described in more detail below.…”
Section: Managing Patients With Persistent Symptoms Despite Optimisedmentioning
confidence: 99%
“…Interestingly, mutations in any one of the transporters involved in I − metabolism can cause cancer per se (Russo et al 2001, Schubert et al 2014, Huang & Jap 2015. In some cases, a mutation may lead to dysfunctions at the plasma membrane and, indirectly, can be associated with tumor progression because of dysregulated protein expression (Dohan et al 2003, De la Vieja et al 2005.…”
Section: Downregulation Of Nis Expression In Thyroid Cancermentioning
confidence: 99%
“…population (Huang & Jap 2015). It seems that these kinds of mutations can change TPO protein activity, its expression in serum, or even the serum levels of TPOAb, confirmed by a study introducing nonsynonymous substitutions in TPO (including p.Ala373Ser, p.Ser398Thr, and p.Thr725Pro) in Bangladeshi patients (Begum et al 2019).…”
Section: Tpomentioning
confidence: 88%